Self-Regulatory Skill Among Children with and without Developmental Coordination Disorder: An Exploratory Study. (1st October 2016) - Sangster Jokić, Claire A.; Whitebread, David
ABSTRACT: Aim: Children with developmental coordination disorder (DCD) experience difficulty learning and performing everyday motor tasks due to poor motor coordination. Recent research applying a cognitive learning paradigm has argued that children with DCD have less effective cognitive and metacognitive skills with which to effectively acquire motor skills. However, there is currently limited research examining individual differences in children's use of self-regulatory and metacognitive skill during motor learning. This exploratory study aimed to compare the self-regulatory performance of children with and without DCD. Methods: Using a mixed methods approach, this study observed and compared the self-regulatory behavior of 15 children with and without DCD, aged between 7 and 9 years, during socially mediated motor practice. Observation was conducted using a quantitative coding scheme and qualitative analysis of video-recorded sessions. This paper will focus on the results of quantitative analysis, while data arising from the qualitative analysis will be used to support quantitative findings. Results: In general, findings indicate that children with DCD exhibit less independent and more ineffective self-regulatory skill during motor learning than their typically developing peers. In addition, children with DCD rely more heavily on external support for effective regulation and are more likely to exhibit negative patterns of motivational regulation. Conclusions: These findings provide further support for the notion that children with DCD experience difficulty effectively self-regulating motor learning. Implications for practice and directions for future research are discussed.